Carvacrol: An in silico approach of a candidate drug on HER2, PI3Kα, mTOR, HER-α, PR, and EGFR receptors in the breast cancer - Herrera-Calderon, Oscar (2020)
Carvacrol is a phenol monoterpene found in aromatic plants specially in Lamiaceae family, which has been evaluated in an experimental model of breast cancer. However, any proposed mechanism based on its antitumor effect has not been reported. In our previous study, carvacrol showed a protective effect on 7,12-dimethylbenz[α]anthracene- (DMBA-) induced breast cancer in female rats. The main objective in this research was to evaluate by using in silico study the carvacrol on HER2, PI3Kα, mTOR, hERα, PR, and EGFR receptors involved in breast cancer progression by docking analysis, molecular dynamic, and drug-likeness evaluation. A multilevel computational study to evaluate the antitumor potential of carvacrol focusing on the main targets involved in the breast cancer was carried out. The in silico study starts with protein-ligand docking of carvacrol followed by ligand pathway calculations, molecular dynamic simulations, and molecular mechanics energies combined with the Poisson–Boltzmann (MM/PBSA) calculation of the free energy of binding for carvacrol. As result, the in silico study led to the identification of carvacrol with strong binding affinity on mTOR receptor. Additionally, in silico drug-likeness index for carvacrol showed a good predicted therapeutic profile of druggability. Our findings suggest that mTOR signaling pathway could be responsible for its preventive effect in the breast cancer.